The Future is Wide Open: Sustainable Scholarly Communications and Affordable Learning in Libraries. Issue 2 (3rd July 2019) - Krier, Laura; Premo, Rita; Wegmann, Mary
Abstract: Our current scholarly publishing model is not sustainable. Librarians need to engage our academic communities in a shift toward open access models. It will involve new work, new positions in libraries, and significant changes to roles within our institutions. In this commentary, the authors lay out why this shift is necessary and what it might entail for libraries and library resources. They describe their library's increasing role in supporting and advocating for open access and open educational resources through participation in campus affordable learning initiatives, working with disciplinary faculty in new ways to draw attention to open access resources.